Złudzenie życia. (Gdynia : [s.n.], 1946)
Afisz filmu, który był wyświetlany w gdyńskim kinie ok. kwietnia 1946 r.
Keywords: Kina -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Kino amerykańskie -- 1929-1945 -- druki ulotne